PEDAGOGIK OLIY TA’LIMDA BOʻLAJAK INGLIZ TILI MUTAXASSISLARI-TALABALARNING YOZUV KOMPETENSIYASINI TAKOMILLASHTIRISH KONSEPSIYASI - Azizov, S. (SCIENCE and SOCIETY, 2023)
Among the types of speech activity in language education, the role of writing differs in a number of practical aspects, and these practical aspects determine the actual significance of the writing competence of students in the target foreign language studying at a pedagogical university. In this article, the author examines the role of a written speech along with the concept of the educational environment in the same process based on the requirements of today.
Keywords: writing competence; higher education; English language; writing; concept; writing skill; productive skill; teacher education; language education; text; context; language competence